Redox‐Switchable 20π‐, 19π‐, and 18π‐Electron 5, 10, 15, 20‐Tetraaryl‐5, 15‐diazaporphyrinoid Nickel(II) Complexes. (8th January 2016) - Satoh, Takaharu; Minoura, Mao; Nakano, Haruyuki; Furukawa, Ko; Matano, Yoshihiro
Abstract: The first examples of air‐stable 20π‐electron 5, 10, 15, 20‐tetraaryl‐5, 15‐diaza‐5, 15‐dihydroporphyrins, their 18π‐electron dications, and the 19π‐electron radical cation were prepared through metal‐templated annulation of nickel(II) bis(5‐arylamino‐3‐chloro‐8‐mesityldipyrrin) complexes followed by oxidation. The neutral 20π‐electron derivatives are antiaromatic and the cationic 18π‐electron derivatives are aromatic in terms of the magnetic criterion of aromaticity. The meso N atoms in these diazaporphyrinoids give rise to characteristic redox and optical properties for the compounds that are not typical of isoelectronic 5, 10, 15, 20‐tetraarylporphyrins.